Osebnostne poteze v otroštvu - Zupančič, Maja (Šolsko polje, 2010)
The contribution presents relations between mid-level personality traits and indicators of children's cognitive characteristics at the entry to a nine-year elementary school, i. e. general non-verbal cognitive ability, early literacy, and numeracy concepts and skills. A multiple-informant method was used in obtaining data on personality. Trait ratings were gathered for 108 Slovene children longitudinally (across one-year time intervals) and data for 22 children was collected concurrently aft er the school entry. In general, parent reports on child personality traits signifi cantly predict firstgraders' cognitive characteristics, but the predictive value is relatively weak while child personality trait expression based on teachers' assessments appears moderately predictive. Contemporaneous associations between firstgraders' cognitive attributes and personality ratings are stronger than longitudinal ones; on-entry basic skills and non-verbal ability can be predicted as early as at age three and five, respectively. Across the informant groups and child age, the cognitive characteristics in the first year of schooling are consistently predicted by adult reports on the perceived child trait intelligence. The effect size and the remaining links between personality traits and child cognitive characteristics are similar to those reported in adult samples: the marker traits of extraversion, neuroticism and agreeableness are negatively related to measures of cognitive competence.
Keywords: childhood; firstgraders; nebesedna spoznavna sposobnost; non-verbal cognitive ability; on-entry baseline assessment; osebnostne poteze; otroštvo; personality traits; prvošolci; temeljne kompetentnosti; vstop v šolo; vzgoja in izobraževanje